2001
DOI: 10.1074/jbc.m103034200
|View full text |Cite
|
Sign up to set email alerts
|

A Ca2+-activated NADPH Oxidase in Testis, Spleen, and Lymph Nodes

Abstract: Superoxide and its derivatives are increasingly implicated in the regulation of physiological functions from oxygen sensing and blood pressure regulation to lymphocyte activation and sperm-oocyte fusion. Here we describe a novel superoxide-generating NADPH oxidase referred to as NADPH oxidase 5 (NOX5). NOX5 is distantly related to the gp91 phox subunit of the phagocyte NADPH oxidase with conserved regions crucial for the electron transport (NADPH, FAD and heme binding sites). However, NOX5 has a unique N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
530
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(556 citation statements)
references
References 58 publications
19
530
1
6
Order By: Relevance
“…Despite advances in Nox research, progress in Nox5 biology, especially in the cardiovascular system, in in vivo settings , has been slow because of lack of research tools and experimental models. Nox5 was originally identified in testis, ovaries, spleen, and immature lymphocytes and is heavily expressed in various cancers 17. More recently, Nox5 has been demonstrated in the vascular system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite advances in Nox research, progress in Nox5 biology, especially in the cardiovascular system, in in vivo settings , has been slow because of lack of research tools and experimental models. Nox5 was originally identified in testis, ovaries, spleen, and immature lymphocytes and is heavily expressed in various cancers 17. More recently, Nox5 has been demonstrated in the vascular system.…”
Section: Discussionmentioning
confidence: 99%
“…During evolution, for unknown reasons, the Nox5 gene was lost in rodents, but is present and functionally active in some invertebrates and in higher mammals 17. Arthropods possess Nox5, an ortholog of human Nox5, besides dual oxidase, and some of them also possess Nox4‐art, a gene related to Nox4 31, 49.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human and rodent VSM cells, Nox1 and Nox4 expression have been documented [65,80,98,140,163], and Nox2 expression has also been reported in some human VSM cells [79,155]. Nox5 may be expressed in human VSM cells but not in rodent [8].…”
Section: Regulation Of Nadph Oxidasementioning
confidence: 99%
“…This process has been shown to significantly contribute to intracellular acidification in phagocytes [5;6]. To counteract the cytosolic acidification during NADPH oxidation, it has been suggested that NADPH oxidase functions at the same time as a H + channel to support H + release from cells [7], and recombinant expression of several NADPH oxidase isoforms have been shown to result in a plasma membrane H + conductance, including Nox2 [8], Nox5 [9], and a truncated form of Nox1 [1]. However, this conclusion was challenged early on owing to i) the expression of the Nox constructs in cell systems that already expressed native H + currents, ii) a lack of H + selectivity of the resulting currents, and iii) the much shorter time constants of current activation recorded after Nox expression in these studies when compared to time constants of native H + currents [10;11].…”
Section: Introductionmentioning
confidence: 99%